Civil War Ghost Stories & Legends - Roberts, Nancy, 1924-2008 (Book collections on Project MUSE., 1992)
Presents eighteen tales of the supernatural involving major battlefields and other sites in the Civil War, including Gettysburg, Antietam, Andersonville, and Harpers Ferry.